PELATIHAN PERANCANGAN DAN PEMBUATAN MEJA SAJI BERBAHAN BESI NAKO DAN KAYU LAPIS MENGGUNAKAN METODE PENGELASAN KEPADA PERMUDHITA UNTUK FASILITAS PASRAMAN KERTAJAYA TANGERANG - I Wayan Sukania; Lamto Widodo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Observations in Pasraman Kertajaya Tangerang showed that the need for a table is very urgent. Whenever there is a religious event, it is always busy with making a serving table from a school bench. Of course, the appearance is not good. Therefore, the manager of Pasraman welcomed the idea of making the serving table. To bridge the need for an improved design and product design skills, especially serving tables and efforts to improve the skills of using iron welding equipment and wood processing equipment by Permudhita, and to meet the needs of a serving table at Pasraman Kertajaya Tangerang, it is felt very necessary to hold this PKM activity. PKM activities are divided into 2 sessions namely design theory sessions and practical sessions. The first session was in the form of a brief theory regarding the stages of product design especially the serving table. The first session resulted in several serving table designs and was selected for the best practice material. While the second session was a direct practice of making a serving table using equipment that was provided at the training venue. The absorption of knowledge and skills is measured by the questionnaire. The initial questionnaire is to find out the initial ability and the final questionnaire to know the additional ability of the participants. The result turned out to be an increase in the insights and skills of the participants. Based on the results of the initial questionnaire about 60% of the participants had the ability to match the questions on the questionnaire. However, after the practice of knowledge and skills, the participants changed to 100% of the questions in the questionnaire. To the instructor's guide in training, all participants said that it was easy to understand. In connection with the addition of technical knowledge of the participants after the training, it was found that an average of 81% of the technical knowledge of the participants increasedABSTRAK:Pengamatan di Pasraman Kertajaya Tangerang menunjukkan bahwa kebutuhan terhadap meja saji sangat mendesak. Setiap ada acara keagamaan selalu disibukkan dengan membuat meja saji dari bangku sekolah yang disusun. Tentu penampilan kurang baik. Oleh karena itu pengelola pasraman menyambut sangat baik ide pembuatan meja saji tersebut. Untuk menjembatani adanya kebutuhan akan peningkatan ketrampilan mendisain dan merancang produk khususnya meja saji serta usaha peningkatan keterampilan menggunakan peralatan pengelasan besi dan peralatan pengolah kayu oleh para Permudhita, serta untuk memenuhi adanya kebutuhan meja saji di Pasraman Kertajaya Tangerang maka dirasakan sangat perlu menyelenggarakan kegiatan PKM ini. Kegiatan PKM dibagi kedalam 2 sesi yaitu sesi teori perancangan dan sesi latihan atau praktik. Sesi pertama berupa teori singkat mengenai tahapan perancangan produk khususnya meja saji. Sesi pertama menghasilkan beberapa disain meja saji dan selanjunya dipilih yang ternaik untuk materi praktik. Sedangkan sesi kedua adalah praktik langsung membuat meja saji menggunakan peralatan yang telah disediakan di tempat pelatihan. Daya serap ilmu dan keterampilan diukur dengan kuisioner. Kuisioner awal untuk mengetahui kemampuan awal dan kuisioner akhir uantuk mengetahui tambahan kemampuan para peserta. Hasilnya ternyata ada peningkatan wawasan dan keterampilan dari para peserta. Berdasarkan hasil kuisioner awal sekitar 60% para peserta memiliki kemampuan sesuai dengan pertanyaan pada kuisioner. Namun setelah praktik pengetahuan dan keterampilan peserta berubah mejadi 100 % terhadapat pertanyaan pada kuisioner. Terhadap panduan instruktur dalam pelatihan, semua peserta mengatakan mudah dipahami. Berkaitan dengan adanya penambahan pengetahuan teknik para peserta setelah pelatihan, diketahui bahwa rata-rata 81% pengetahuan teknik para peserta bertambah